„Rojenia międzyanatomiczne” i „anagramy ciała”: Konstanty A. Jeleński i prace Hansa Bellmera - Swoboda, Bartosz (Przestrzenie Teorii, 2022)
The aim of this article is to discuss and analyze an extensive essay by Konstanty A. Jeleński, entitled Bellmer albo anatomia miłości fizycznej i nieświadomości [Bellmer or the anatomy of physical love and the unconsciousness], devoted to the works of Hans Bellmer, a German painter, drawer and writer. The article presents the scope and nature of artistic activities undertaken by Bellmer and the way in which these activities and works were described and interpreted by Jeleński. The aim of the article is to show the basic contexts in which Jeleński placed controversial and ambiguous works by the German artist. The article also mentions the main interpretative keys Jeleński uses to show the creative philosophy and uncover the secrets of artistic expression, especially the mechanisms of perceiving the body and visual manifestations of unconsciousness which come to the fore in Bellmer’s works.